Clinical features of 22q11.2 deletion syndrome related to hearing and communication. (1st September 2020) - Suzuki, Noriomi; Kanzaki, Sho; Suzuki, Takafumi; Ogawa, Kaoru; Yamagishi, Hiroyuki
Abstract: Background: Individuals with 22q11.2 deletion syndrome (22q11.2DS) exhibit various phenotypes. Objective: To compare the clinical and otorhinolaryngological features of Japanese patients with 22q11.2DS with those of patients reported in Western literature. Materials and methods: We retrospectively assessed the medical records of 17 Japanese patients with 22q11.2DS and compared our findings with previously reported findings in Western literature. Results: Hearing loss was the most frequent complaint ( n  = 8, 47%), followed by articulation disorders and/or nasopharyngeal closure failure ( n  = 4, 24%) and language development delay ( n  = 2, 12%). Ten patients (59%) had hearing loss regardless of the chief complaint (total 15 ears – mild, 9; moderate, 6). Four patients had bilateral hearing loss. One patient (6%) underwent tympanostomy tube placement for refractory exudative otitis media, another (6%) underwent myringoplasty, and three patients (18%) underwent tympanoplasties for chronic otitis media or middle ear malformation. Previous studies in Western countries reported similar results in terms of frequency of hearing loss, severity of hearing loss, and the percentage of middle ear malformations. Conclusions: The otorhinolaryngological characteristics of Japanese patients with 22q11.2DS were similar to those in Western countries. Hearing loss was primarily caused by disorders like otitis media and middle ear malformation. Significance: Our findings may aid treatment planning for Asian patients with 22q11.2DS.